Growth in the Shadows: Effect of the Shadow Economy on U.S. Economic Growth over More Than a Century - Rajeev K. Goel; James W. Saunoris; Friedrich Schneider (Institute of Labor Economics (IZA), 2017)
This paper provides a long-term view by studying the effect of the underground or shadow economy on economic growth in the Unites States over the period 1870 to 2014. Shadow activities might spur or retard economic growth depending on their interactions with the formal sector and impacts on the provision of public goods. Nesting the analysis in a standard neo-classical growth model, we use a relatively new time-series technique to estimate the short-run dynamics and long-run relationship between economic growth and its determinants. Results suggest that prior to WWII the shadow economy had a negative effect on economic growth; however, post-WWII the shadow economy was beneficial for growth. This ambiguity regarding the overall growth impact of the shadow economy is consistent with underlying theoretical arguments.
Keywords: E26; O43; O51; K42; 330; economic growth; shadow economy; United States; time series